The future of personal financial planning: A case study on Fintech is revolutionizing Personal Finance through technologies - Ab Rahman, Siti Maziah; Shaari, Rustam; Yasin , Ahmad Bukhari; Wan Muhammad, Wan Firdaus; Mat Rusok, Nur Hazelen (Journal of Islamic, Social, Economics and Development, 2025)
Fintech is revolutionizing personal finance management, empowering individuals to achieve greater control over their financial futures. In an era where managing personal finances is as crucial as earning money, fintech has emerged as a pivotal ally, significantly enhancing budgeting, investing, and spending. Fintech offers unprecedented access, efficiency, and security in managing finances, shifting control and management of finances into the hands of consumers. The study highlights the enhanced accessibility, personalized financial management tools, and increased financial inclusion facilitated by FinTech solutions. It addresses challenges such as funding limitations, cybersecurity threats, and regulatory hurdles. The analysis indicates that FinTech is revolutionizing financial ecosystems by promoting efficiency, customization, and broader inclusion, paving the way for a more empowered and user-centric financial future. Furthermore, the report emphasizes FinTech's role in improving financial literacy through tailored advice and educational resources, enabling consumers to navigate increasingly complex financial landscapes with greater confidence. This study explores the transformative impact of Fintech on personal financial planning, highlighting the integration of technologies such as AI, blockchain, and automation platforms. Fintech tools are redesigning how people manage money, from automating budgeting to offering personalized investment guidance. AI-driven budgeting tools and robo-advisors provide real-time insights and automate processes like expense tracking and portfolio optimization. Blockchain technology enhances transparency and reduces fraud through decentralized ledger systems2. These innovations streamline financial counseling, making services more accessible and affordable. The study identifies challenges including data security concerns, the necessity for regulatory advancement, and ensuring consumer protection, transparency, and equitable practices. The future of financial planning will likely hinge on balancing technological innovation with the need for human insight and personalized service.